Strengthening Global Health Security: A Review of Lessons Learnt from Indonesia's COVID-19 Response - Dicky Budiman; Ernawanti Ernawanti; Cordia Chu (International Journal of Advanced Health Science and Technology, 2023)
The COVID-19 pandemic has revealed how poorly prepared the world is for a pandemic and how easily viruses spread in our interconnected world. The response to COVID-19 in Indonesia has been hampered by a surge in infection and re-infection cases, an ill prepared of healthcare system, low booster vaccination coverage, the emerging of new sub variant, inconsistent implementation of public health measures, and communication barriers. Nevertheless, as infectious disease outbreaks become more frequent, it is hoped that national health security resources will be identified and strengthened. This will enable the nation to keep pace with spreading diseases and become more resilient to future threats. COVID-19 exposes strengths and weaknesses while also creating threats and opportunities. An analysis of the COVID-19 pandemic strategy was conducted using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis based on Indonesia's experience with the response and countermeasures to COVID-19. The objective of this study is to analyse all the factors involved in the COVID-19 pandemic response so that lessons can be learned towards an effective public health emergency response. The results highlighted strengths, identified weaknesses, and provided recommendations for the future. This would be useful in responding to current threats to global health security and preparing for future ones.